Epigenome‐wide analyses identify DNA methylation signatures of dementia risk. Issue 1 (10th August 2020) - Walker, Rosie M.; Bermingham, Mairead L.; Vaher, Kadi; Morris, Stewart W.; Clarke, Toni‐Kim; Bretherick, Andrew D.; Zeng, Yanni; Amador, Carmen; Rawlik, Konrad; Pandya, Kalyani; Hayward, Caroline; Campbell, Archie; et al.
Abstract: Introduction: Dementia pathogenesis begins years before clinical symptom onset, necessitating the understanding of premorbid risk mechanisms. Here we investigated potential pathogenic mechanisms by assessing DNA methylation associations with dementia risk factors in Alzheimer's disease (AD)–free participants. Methods: Associations between dementia risk measures (family history, AD genetic risk score [GRS], and dementia risk scores [combining lifestyle, demographic, and genetic factors]) and whole‐blood DNA methylation were assessed in discovery and replication samples (n = 400 to 5000) from Generation Scotland. Results: AD genetic risk and two dementia risk scores were associated with differential methylation. The GRS associated predominantly with methylation differences in cis but also identified a genomic region implicated in Parkinson disease. Loci associated with dementia risk scores were enriched for those previously associated with body mass index and alcohol consumption. Discussion: Dementia risk measures show widespread association with blood‐based methylation, generating several hypotheses for assessment by future studies.